Key compounds contributing to the fruity aroma characterization in Japanese raw soy sauce. Issue 10 (3rd October 2017) - Meng, Qi; Imamura, Miho; Katayama, Hiroshi; Obata, Akio; Sugawara, Etsuko
Abstract: In order to clarify the aroma characteristics of raw soy sauce (RS), the application of gas chromatography−olfactometry analysis to the aroma concentrate from a RS revealed 76 aroma peaks, of which 25 peaks showed fruit-like aromas. Furthermore, the head space aromatic compounds of RS were analyzed with 32 peaks detected. Ethyl 2-methylpropanoate, ethyl butanoate, ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, and ethyl 4-methylpentanoate were detected with higher flavor dilution factor (FD factor) than other aroma compounds by aroma extract dilution analysis. Quantitative analysis suggested that these compounds were common in all RS samples tested in this study, and were present at higher concentrations than their perception thresholds. The concentrations and the FD factors of these compounds were significantly decreased during the heating of the RS. Fruitiness is one of the key aroma characteristics of RS and the ethyl esters identified in this study are the key components contributing to this distinct aroma. Graphical abstract: : Fruitiness is one of the key aroma characteristics of raw soy sauce and the ethyl esters identified in this study are the key components contributing to this distinct aroma.